2017
DOI: 10.1039/c6mt00270f
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of metal concentrations and copper isotope ratios in the G93A SOD1 mouse model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a motor neuron disease, which involves progressive motor neuron degeneration in the central nervous system (CNS). The G93A SOD1 mouse model simulates one of the most common causes of familial ALS through the overexpression of a mutated form of the human gene encoding copper/zinc superoxide dismutase (SOD1). Transition metals, particularly Cu and Zn, have been shown to behave abnormally in the disease context and have been hypothesized to contribute to and potentially trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 135 publications
(195 reference statements)
6
18
0
Order By: Relevance
“…In relation to this, alterations in copper influx/efflux have been evidenced in the SOD1-G93A mice. In particular, elevated concentrations of copper in this mutant SOD1 model have been reported early at pre-symptomatic phases within the SC and skeletal muscles, and this condition aggravates as disease progresses (Refs 60, 61), suggesting that copper dyshomeostasis might facilitate the development of ALS. Further, studies in mice with genetic modifications in copper-handling enzymes have confirmed the putative role of copper homeostasis in SOD1 toxicity.…”
Section: Mechanistic Insights Into the Role Of Copper Dysregulation Imentioning
confidence: 81%
“…In relation to this, alterations in copper influx/efflux have been evidenced in the SOD1-G93A mice. In particular, elevated concentrations of copper in this mutant SOD1 model have been reported early at pre-symptomatic phases within the SC and skeletal muscles, and this condition aggravates as disease progresses (Refs 60, 61), suggesting that copper dyshomeostasis might facilitate the development of ALS. Further, studies in mice with genetic modifications in copper-handling enzymes have confirmed the putative role of copper homeostasis in SOD1 toxicity.…”
Section: Mechanistic Insights Into the Role Of Copper Dysregulation Imentioning
confidence: 81%
“…The blood Cu isotopic composition has been shown to become lighter during ageing in a remote human Yakut population [25], and experiments on ageing C. elegans have confirmed this finding [26]. Copper isotopic compositions are highly sensible to disease conditions and have been investigated as a new biomarker for Wilson disease [27,28], cancer [29,30], liver diseases [24,31] and neurodegenerative disorders [32][33][34][35].…”
Section: Introductionmentioning
confidence: 94%
“…indicate accumulation of Cu in the spinal cord (Li et al, 2006;Tokuda et al, 2015Tokuda et al, , 2014Tokuda et al, , 2013Tokuda et al, , 2008 at single time points, as well as over time (Tokuda et al, 2009(Tokuda et al, , 2007. Brain tissue showed a similarly varied behavior with studies reporting both elevated concentrations (Hilton et al, 2016), or no change to healthy controls (Enge et al, 2017;Lelie et al, 2011;Li et al, 2006;Tokuda et al, 2009Tokuda et al, , 2007. These changes in Cu and Zn concentrations have been postulated to play an important role in the toxic-gain-of-function associated with mSOD1 (Borchelt et al, 1994;Hilton et al, 2015).…”
Section: A C C E P T E Dmentioning
confidence: 97%
“…While the accumulation and/or depletion of metals in different tissues reported in the literature are inconsistent, overall there appears to be accumulation in tissues of diseased mice. Tissues associated with the autonomic nervous system (ANS) have been shown to accumulate Cu and Zn (Enge et al, 2017;Hilton et al, 2016), with muscle tissue demonstrating pre-symptomatic increases in concentrations (Enge et al, 2017). Results from central nervous system (CNS) tissues…”
Section: A C C E P T E Dmentioning
confidence: 99%